Language Brain Representation in Bilinguals With Different Age of Appropriation and Proficiency of the Second Language: A Meta-Analysis of Functional Imaging Studies - Cargnelutti, Elisa; Tomasino, Barbara; Fabbro, Franco (Frontiers in Human Neuroscience, 2019)
Language representation in the bilingual brain is the result of many factors, of which age of appropriation (AoA) and proficiency of the second language (L2) are probably the most studied. Many studies indeed compare early and late bilinguals, although it is not yet clear what the role of the so-called critical period in L2 appropriation is. In this study, we carried out coordinate-based meta-analyses to address this issue and to inspect the role of proficiency in addition to that of AoA. After the preliminary inspection of the early (also very early) and late bilinguals’ language networks, we explored the specific activations associated with each language and compared them within and between the groups. Results confirmed that the L2 language brain representation was wider than that associated with L1. This was observed regardless of AoA, although differences were more relevant in the late bilinguals’ group. In particular, L2 entailed a greater enrollment of the brain areas devoted to the executive functions, and this was also observed in proficient bilinguals. The early bilinguals displayed many activation clusters as well, which also included the areas involved in cognitive control. Interestingly, these regions activated even in L1 of both early and late bilingual groups, although less consistently. Overall, these findings suggest that bilinguals in general are constantly subjected to cognitive effort to monitor and regulate the language use, although early AoA and high proficiency are likely to reduce this.